ANALISIS IMPLEMENTASI GOOD GOVERNANCE PADA PENGELOLAAN KEUANGAN DESA SEPANGAH KECAMATAN AIR BESAR KABUPATEN LANDAK - Risal; Dowi Sinta, Fiyo (Jurnal Akuntansi, Auditing dan Investasi, 2023)
This study aims to see how good governance is implemented in the aspects of Transparency,Accountability and Public Involvement in the management of village funds. By using a qualitativedescriptive method, the technical analysis used is through the In-depth Interview technique whichconsists of three stages, namely Data Reduction, Data Presentation and Drawing Conclusions. Basedon the results of the research conducted, it shows that the Good Governance of Village FundManagement in Sepangah Village is guided by Landak District Regent Regulation Number 62 of 2020.From a transparency perspective, it has not been fully implemented, where there are no announcementboards or information boards that can be accessed by the village community. In the aspect ofAccountability, it has been guided by the Regulations, it's just that in accountability reports, it still oftenexperiences delays due to a lack of human resources and knowledge of computer mastery which is anobstacle. And seen from the aspect of Public Involvement the Sepangah village government has beencarried out in accordance with regulations wherein every deliberation held has involved villageinstitutions in planning development decision-making as well as the community participating in mutualcooperation.